Agricultural flash droughts and their impact on crop yields in southeastern South America - Lovino, Miguel Angel (2025)
This study investigates the characteristics of agricultural flash droughts (AFDs) and their impacts on critical growth periods of soybean and corn in southeastern South America (SESA). Using ERA5 data from 1960 to 2022, we examine AFD frequency, duration, intensity, trends, seasonality, life cycle, and the influence of land–atmosphere interactions. Historical crop data, spanning different time periods across SESA countries, are analyzed to assess how the spatiotemporal evolution and varying life cycles of AFDs affect crop yields. The highest AFD frequencies (3–8 events per decade) occur in the central portion of SESA. These rapidly intensifying events often evolve into seasonal droughts lasting 1.5–3 months. Although area-averaged AFD frequency shows no significant change in central SESA, positive trends are noticeable in southern Brazil and Uruguay. Towards the north of SESA, AFDs are less frequent, with 1–3 episodes per decade, although the frequency has significantly increased since 1970. AFDs tend to last over 3 months and reach higher intensity. Land–atmosphere feedback mechanisms are reflected in high positive vapor pressure deficit and temperature anomalies that exacerbate soil moisture deficits despite a relatively stable precipitation deficit, accelerating AFD intensification periods. AFDs typically impact smaller areas, while slow-evolving droughts affect larger regions. However, AFDs´ timing during the critical growth periods of the crops can lead to substantial yield losses. In central SESA, AFDs mainly occur between November and January, affecting both crops during their flowering and grain filling in December and January. In northern SESA, AFDs occur later, from February to April, primarily impacting second-season corn. The overall impact on crop yields depends on the duration, spatial extent, and intensity of the drought after its intensification.